THE RELATIONSHIP BETWEEN SOCIO - ECONOMIC FACTORS AND RISK OF STUNTING : A SYSTEMATIC REVIEW - M. Hadi, (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Stunting describes a chronic nutritional problem that is influenced by the condition of the mother/prospective mother, fetus and baby, including diseases during infancy. Stunting is not only related to health problems but is also affected by various other conditions that indirectly affect health. Aim: The goal of this study is to showed the relationship between socio - economic factors and risk of stunting.Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 119 articles, whereas the results of our search on SagePub brought up 87 articles. The results of the search conducted for the last year of 2013 yielded a total 18 articles for PubMed and 12 articles for SagePub. In the end, we compiled a total of 24 papers, 15 of which came from PubMed and 9 of which came from SagePub. We included six research that met the criteria. Conclusion: Consistently, socio-economic status greatly influences the nutritional status of children, while the level of education and knowledge of the mother is the most influential.